Musical Performance in the Context of the Development of Contemporary Musical Art - BATOVSKA, Olena; GREBENUK, Natalia; KOSTOGRYZ, Sergii; DYACHENKO, Yuriy; TKACHENKO, Victoria (Studia Universitatis Babes-Bolyai Musica, 2024)
The study aims to determine the specifics of musical performance in the context of the development of contemporary music, considering various musical genres. The methods of analysis, comparison, calculation of the Cronbach's coefficient, and Fisher criterion were used to achieve this goal. It has been established that the most characteristic elements of classical music are an academic approach to interpretation and the embodiment of artistic and aesthetic components. It has been proven that the characteristic features of contemporary music performance are improvisation (α=0.837), emotional expressiveness (α=00.823), and non-standard note combinations (0.819). The practical significance of the work lies in the possibility of using the established features of musical genres for their qualitative interpretation during the educational process.